Determinants of Magnesium Intake, Zinc Intake and Body Mass Index (BMI) with Fasting Blood Glucose Levels in the Elderly in Klaten Regency - Aruni Aruan; Anik Lestari; Eti Poncorini Pamungkasari (GoAcademica Research & Publishing, 2023)
The International Diabetes Federation (IDF) estimates that the number of diabetics in Indonesia will reach 28.57 million (2045) from 19.47 million (2021). One of the populations that is susceptible to diabetes is the elderly due to decreased organ function. This is a challenge due to the increasing global and Indonesian elderly populations. This study used a cross-sectional design. The subjects of this study were the elderly (≥ 60 years), as many as 158 people with inclusion criteria. Sampling using multistage random sampling technique. Characteristic data obtained from interviews. BMI was obtained from anthropometric measurements (height and weight). Intake of magnesium and zinc was obtained from 2 times food recal 24 hour and SQ FFQ. Fasting blood sugar data obtained from fasting blood sugar examination. Statistical analysis using multiple linear regression. The results showed that the three variables (Magnesium intake, zinc intake, BMI) could have an effect on fasting blood sugar by 7.2%. The model that occurs is GDP = 150.4 + (1.708*BMI) + (-4.16*Intake of Magnesium) + (-0.063*Intake of Zinc). From this model it can be suggested that the elderly consume foods rich in magnesium and zinc and control BMI to avoid increasing fasting blood sugar levels.